Chelation and nanoparticle delivery of monomeric dopamine to increase plant salt stress resistance - Jiang Du; Huazhen Xu; Da-xia Zhang; Shouqian Feng (Nature Communications)
Abstract Soil salinization hinders sustainable development of global agriculture. Dopamine (DA) delivery is promising for mitigating the detrimental effects of salt on plants. However, self-polymerization limits delivery and effectiveness. Here we chelated DA with ethylenediamine tetraacetic acid and zinc to reduce self-polymerization. To reduce soil adsorption, a sodium lignosulfonate and octadecyl dimethyl benzyl ammonium chloride nanocarrier is made for delivery to the plant. Compared with DA monomer, the soil adsorption rate of the DA in the nanocarrier is 46.02% lower. Salt stress experiments reveal, compared with NaCl and DA groups, the nanocarrier group exhibits significant increases in growth indicators for tomato plants. The beneficial effect is attributed to the increases in proline content, antioxidant capacity, and K+/Na+ ratios in the plants. Similar results are also observed with woody pear seedlings. These findings provide insights into alleviating crop salt stress.